İşçi avukatlık - Şahinkaya, Nilgün (My University, 2019)
Avukatlık mesleği, ekonomik gelişmelerin etkisi ile dönüşüme uğramış, işçi avukatlıkyaygınlaşmış, işçi avukat sayısı birçok ülkede ve ülkemizde son 30 yılda artmıştır.Avukatın “işçi” kavramı ile ifade edilmesi henüz tartışma aşamasındadır. Buradamesleki statüyü koruma kaygısı ile işçiliğin avukatlık mesleğinin özüne zarar vereceğikaygısı göze çarpmaktadır. İşçileşme süreci avukatlığın serbest meslek olma vebağımsız olma niteliklerini ortadan kaldırmakta, teknisyenleşme, yoksullaşma gibisüreçlerin yaşanmasına neden olmakta, işçi avukatın sorumluluğu ile ilgili sorunlarortaya çıkarmakta, işçi avukatın kanundan ve meslek ilkelerinden kaynaklı hak vesorumlulukları konusunda da tartışma yaratmaktadır. Avukatlar arası iş hukukuuyuşmazlıkları yaygınlaşmaktadır. Avukatlık alanında meslek hukuku ile iş hukukuarasında sıkışmış bir durum söz konusudur. Güncel mevzuat, avukatlık alanındayaşanan dönüşümü karşılamakta yetersizdir. Gelinen aşamada TBB yapılan düzenleyiciişlemler yargı kararları ile iptal edilmiş olup, gerek yasa koyucu gerek meslekörgütlerince, mevzuat tasarıları oluşturulmakta ve bunlar tartışmaya açılmaktadır

Economic developments have caused a transformation in attorneyshipprofession, so the employed attorneyship has become prevalent and the number ofemployed attorney has increased in many countries and Turkey in the last 30 years. Theexpression of lawyer with the concept of “employed” is still under discussion. Here theoutstanding issue is the concern for protection the profession and fear about thepossibility of damage given by workmanship to attorneyship profession. The process inwhich attorneys become workers eliminates all qualities to be self-employed andindependent, and causes a basis on which attorneys transforms into a pauper technician.Such process creates issues about employed attorney’s responsibility and sparks adebate about employed attorney’s rights and liabilities rooted in law. The disputes aboutlabour law become common among attorneys. Attorneyship is in a situation in which itis caught between labour law and occupational law. Current statute is insufficient inmeeting the requirements of transformation experienced in the field of attorneyship. Atthis stage, regulatory procedures adopted by Union of Turkish Bar Associations havebeen cancelled with judicial decisions, so today statutory drafts are formed and broughtup for discussion by both legislator and professional organisation.
Keywords: İşçi avukatlık employed attorneyship